Statins and Histone Deacetylase Inhibitors Affect Lamin A/C – Histone Deacetylase 2 Interaction in Human Cells - Mattioli, Elisabetta; Andrenacci, Davide; Mai, Antonello; Valente, Sergio; Robijns, Joke; De Vos, Winnok H.; Capanni, Cristina; Lattanzi, Giovanna (Frontiers in Cell and Developmental Biology, 2019)
We recently identified lamin A/C as a docking molecule for human histone deacetylase 2 (HDAC2) and showed involvement of HDAC2-lamin A/C complexes in the DNA damage response. We further showed that lamin A/C-HDAC2 interaction is altered in Hutchinson-Gilford Progeria syndrome and other progeroid laminopathies. Here, we show that both inhibitors of lamin A maturation and small molecules inhibiting HDAC activity affect lamin A/C interaction with HDAC2. While statins, which inhibit prelamin A processing, reduce protein interaction, HDAC inhibitors strengthen protein binding. Moreover, treatment with HDAC inhibitors restored the enfeebled lamin A/C-HDAC2 interaction observed in HGPS cells. Based on these results, we propose that prelamin A levels as well as HDAC2 activation status might influence the extent of HDAC2 recruitment to the lamin A/C-containing platform and contribute to modulate HDAC2 activity. Our study links prelamin A processing to HDAC2 regulation and provides new insights into the effect of statins and histone deacetylase inhibitors on lamin A/C functionality in normal and progeroid cells.